2005
DOI: 10.1001/archotol.131.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy in N0 Squamous Cell Carcinoma of the Oral Cavity and Oropharynx

Abstract: Objectives: To ascertain the feasibility of sentinel lymph node (SLN) localization by preoperative lymphoscintigraphy and intraoperative gamma probe radiolocalization and to determine the predictive value of the SLN for occult metastasis of the neck in N0 squamous cell carcinoma of the oral cavity and oropharynx. Design: A prospective study of 20 consecutive patients with N0 squamous cell carcinoma of the head and neck who underwent lymphoscintigraphy and SLN biopsy. Interventions: On the day before surgery, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 21 publications
0
45
1
2
Order By: Relevance
“…289 The sensitivity of SLN biopsy for squamous cell carcinoma of the oral cavity and oropharynx is reported to be between 89% and 100% and the false-negative rate 1% to 4%. [287][288][289] Preliminary studies have shown that SLN biopsy is a promising tool for use in patients with early oral and oropharyngeal squamous cell carcinoma. 289,290 These investigations also have shown, however, that multiple, bilateral, or skip SLN may occur.…”
Section: Sentinel Lymph Nodementioning
confidence: 99%
“…289 The sensitivity of SLN biopsy for squamous cell carcinoma of the oral cavity and oropharynx is reported to be between 89% and 100% and the false-negative rate 1% to 4%. [287][288][289] Preliminary studies have shown that SLN biopsy is a promising tool for use in patients with early oral and oropharyngeal squamous cell carcinoma. 289,290 These investigations also have shown, however, that multiple, bilateral, or skip SLN may occur.…”
Section: Sentinel Lymph Nodementioning
confidence: 99%
“…The CT scan and MRI are important technical developments/advancements, helping in determining the presence, extent and local/ regional invasion of tumors 6-8. Investigators also explored the use of Gamma probes for determining occult metastasis in neck with limited success 9,10…”
Section: Introductionmentioning
confidence: 99%
“…PET/CT as a combined modality seems to provide even better results in nodal staging than does PET alone. • Sentinel lymph node detection by preoperative lymphoscintigraphy and intraoperative gamma probe localization has been extensively studied in melanoma and breast cancer, and a recent study has demonstrated very promising results in patients with N0 squamous cell carcinoma (SCC) of the oral cavity and oropharynx, with a negative predictive value of 100% [42].…”
Section: Metastatic Lymphadenopathymentioning
confidence: 99%